Start With Why how great leaders inspire every one to take action - Sinek, Simon (USA Portfolio, 2009)
Why are some people and organisations more innovative, more influential, and more profitable than others? Why do some command greater loyalty from customers and employees alike? Why are so few able to repeat their success over and over? People like Martin Luther King Jr., Steve Jobs and the Wright Brothers might have little in common, but they all started with why. This enabled them to inspire those around them and to achieve remarkable things. In studying the leaders who have had the greatest influence in the world, Simon Sinek discovered that they all think, act and communicate in the same exact way and its complete opposite of what every one else does. Sinek calls this powerful idea The Golden Circle, and it provides a framework upon which organisations can be built, movements can be led, and people can be inspired. And it all starts with WHY.
Keywords: Leadership